2013
DOI: 10.1093/europace/eut059
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vein anatomy predicts freedom from atrial fibrillation using remote magnetic navigation for circumferential pulmonary vein ablation

Abstract: Pulmonary vein anatomy assessed by MDCT is a good predictor of AF recurrence after PVA using RMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 23 publications
2
42
0
2
Order By: Relevance
“…For conventional RF‐based PVI in conjunction with 3D‐electroanatomical mapping, no negative impact on clinical outcomes in the presence of a LCPV was demonstrated and no correlation between PV‐diameters and long‐term clinical failure of PVI was found in two clinical studies . Contrarily to the latter studies, Sohns et al analysed data from 138 consecutive patients with AF referred for PVI with RF energy. With one‐year follow‐up, sinus rhythm was maintained after the initial ablation in 63% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…For conventional RF‐based PVI in conjunction with 3D‐electroanatomical mapping, no negative impact on clinical outcomes in the presence of a LCPV was demonstrated and no correlation between PV‐diameters and long‐term clinical failure of PVI was found in two clinical studies . Contrarily to the latter studies, Sohns et al analysed data from 138 consecutive patients with AF referred for PVI with RF energy. With one‐year follow‐up, sinus rhythm was maintained after the initial ablation in 63% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have investigated PV anatomy with focus on branching pattern, composition, size and ridges [15,16,27]. For comparison, McLellan, et al [16] describe in their study the dimensions of the PV ostia in a group of patients with AF with similar size distribution as in our study.…”
Section: Pulmonary Vein Cross-sectional Areamentioning
confidence: 59%
“…This widely accessible imaging modality may be used to provide a more detailed anatomical evaluation and road map before ablation, in terms of both LA and PV anatomy [3,[7][8][9][10][11][12]. Recent studies indicate that LA and PV characteristics as determined by cardiac MDCT are possible important predictors of AF recurrence after ablation therapy [11,[13][14][15][16], and that the thicker the parts of the LA are, the less successful ablation therapy becomes [13,17]. In addition, it has been found that patients with persistent AF have enlarged LA cavity, decreased left ventricular function and lower success rates than other patients referred for ablation [7,9,18,19].…”
Section: Left Atrial Wall Thickness (Lawt)mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] The association between an LCPV and the outcome of the initial RFCA of AF was also explored by several studies which reported conflicting results. 5,6,[10][11][12] However, to our knowledge, whether or not an LCPV has an influence on the outcome of repeated RFCA for AF has never been discussed and the current study aims to fill in the gap.…”
mentioning
confidence: 99%